A multiple case study on children's study spaces in selected Filipino middle-class homes - Duran, Bianca Ysabelle T.
The study analyzed how residential spaces of Filipino middle income households support children in their studying activities. The study involved households of five middle income families with intermediate elementary school children ranging from 9 to 12 years of age. The families that compose the sample population all reside in Metro Manila. A qualitative research design was utilized given the descriptive nature of the study and a multiple case study approach was conducted. The study used non-probability sampling specifically, purposive sampling to ensure that the participating families would fit the set criteria. The data were gathered through a series of site observations, photo documentation and interviews during home visits. The data were tabulated and coded to discover patterns and prevalent themes and topics that have occurred. Results showed that all participating families did not have designated areas for the purpose of studying and studying alone. All the respondents utilized other areas of the house mostly shared spaces such as the living room and family room for performing activities related to studying. The considerations that influenced the allocation of study spaces within the house were divided into two divisions, namely, physiological and psychosocial factors. The physiological considerations included the temperature or room ventilation, spaciousness, lighting, color scheme, and acoustics, listed in accordance to the importance given by the families. The psychosocial considerations involved encouragement derived from symbolic interior elements such as medals and certificates; security obtained from the presence of other family members in the room where the child studies; and supervision of the parents while the child studies. The result of this study contributes to creating child-friendly spaces for homes and provide significant knowledge for residential and furniture designers as well as educators on how children as well as their parents perceive their homes as a space to study.